Development of Pancen Media in mathematics learning for grade 3 elementary school students - Sapitri, Lindri; Faipri Salegi, Susanti; Imansyah, Farizal (Cendikia : Media Jurnal Ilmiah Pendidikan, 2024)
This research aims to determine the validity and practicality of the development of pancen media in mathematics learning for grade 3 students at SD Negeri 72 Prabumulih. This research is Research and Development (R&D), using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. Data collection was carried out by distributing media expert validation questionnaires, material expert validation, teacher response questionnaires, student response questionnaires individually (one to one) and small groups. Based on the research results, the media expert validation results obtained a percentage of 100% which was categorized as very valid, the results of the material expert validation obtained a percentage of 91.66% with a very valid category, for the results of the practicality of Pancen media, it can be seen from the results of the teacher response questionnaire which obtained a percentage of 100 % was categorized as very practical, the results of the individual student response questionnaire (one to one) obtained a percentage of 88.28% which was categorized as very practical and finally the results of the small group student response questionnaire obtained a percentage of 84.56% with the very practical category. Therefore, it can be concluded that the development of pancen media in mathematics learning for grade 3 elementary school students is declared valid and practical for use in learning.